Konsep dan Aplikasi IPTEK Nuklir di Sekolah Menengah Atas - Mariati -- (Jurnal Pendidikan dan Kebudayaan, 2013)
This study aimed to examine the curriculum at the senior secondary school related to nuclear science and technology in content standards, textbooks, teaching methods, and teacher understanding. Locations determined by purposive sampling in six provinces namely Yogyakarta, East Java, West Nusa Tenggara, East Kalimantan, Riau Islands, and South Sulawesi. The respondent are a teachers of Biology, Physics, and Chemistry respectively 18 people in each province. The research method is a survey and focus group discussion. The study shows that nuclear science content standards are adequate, but the application of nuclear science and technology of today need to be added. Textbooks used is more theory and less contextual of life. Nuclear science and technology learning in general lectures, discussions and giving assignments. Teachers’ understanding of the concepts and applications of nuclear science and technology is still low. The study recommends the present applications of nuclear science and technology need to be added to the content standards, schools need to socialize to the understanding of nuclear science and technology is better, should be made in the book supplements or media-based learning model using information and communication technology to support learning of nuclear science and technology for effective, efficient, and fun learning.ABSTRAK Studi ini bertujuan untuk mengkaji kurikulum Sekolah Menengah Atas tentang ilmu pengetahuan dan teknologi nuklir pada standar isi, buku pelajaran, metode pembelajaran, dan pemahaman guru. Sampling kajian ditentukan secara purposif di enam provinsi, yaitu: Daerah Istimewa Yogyakarta; Jawa Timur; Nusa Tenggara Barat, Kalimantan Timur, Kepulauan Riau, dan Sulawesi Selatan. Responden terdiri atas guru Biologi, Fisika, dan Kimia masing-masing 18 orang setiap  provinsi.  Studi  dilakukan  melalui  survei  dan  focus  group  discussion. Hasil  studi menunjukkan bahwa iptek nuklir pada Standar Isi cukup memadai, namun dalam aplikasi sangat kurang. Ilmu  pengetahuan dan teknologi  nuklir dalam buku  pelajaran lebih banyak  teori dan kurang  kontekstual. Pembelajaran iptek  nuklir  pada  umumnya  dilakukan  dengan  metode ceramah, diskusi, dan penugasan. Pemahaman guru tentang konsep dan aplikasi iptek nuklir masih rendah. Studi merekomendasikan aplikasi iptek nuklir masa kini ditambahkan ke dalam Standar Isi, sekolah perlu melakukan sosialisasi agar pemahaman iptek nuklir lebih baik, begitu juga  perlu menambah  buku suplemen  atau  model pembelajaran  berbasis teknologi  informasi dan komunikasi agar pembelajaran iptek nuklir lebih efektif, efisien, dan menyenangkan.